Le rayonnement spatial des villes tunisiennes à travers la diffusion des entreprises multi-établissements pour l’innovation - Amor Belhedi (Cybergeo, 2007)
The spatial influence of cities is analysed through the innovation diffusion of modern and rare activities, and the network of corresponding firms and their etablishments. The analysis of the diffusion provides information on recent spatial dynamics in Tunisia, the models of this diffusion, the changes brought to the urban hierarchy and the inevitable downgrading of some centers. This text analyzes the innovation diffusion of, modern and rare activities, multi-plant company network in Tunisia between 1997 and 2004. It shows that the spatial diffusion operates mainly at the national level according to a hierarchical process while the proximity works at the regional level. On another level, the city of Sousse reinforces its place contrarily to the second town Sfax whereas the littoral is still privileged by this process, announcing the future Tunisian space.